2019
DOI: 10.1161/jaha.119.014074
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Flow Diverter for the Treatment of Intracranial Aneurysms: A Pilot Study Using a Rabbit Aneurysm Model

Abstract: BackgroundHerein, we report an in vivo study of a biodegradable flow diverter (BDFD) for aneurysm occlusion. Conceptually, BDFDs induce a temporal flow‐diverting effect and provide a vascular scaffold for neointimal formation at the neck of the aneurysm until occlusion. This offers several potential advantages, including a reduced risk of remote ischemic complications and more treatment options in case of device failure to occlude the aneurysm.Methods and ResultsA BDFD consisting of 48 poly‐l‐lactic acid wires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…If the neointimal layer does not cover the bioabsorbable struts evenly, either the stent itself or small segments of PLLA fibers can potentially migrate during fragmentation of polymer in the absorption process, increasing the chance of stroke. The delivery conditions reported in our animal studies resulted in a significant temporary stent diameter reduction of more than four times, yet did not require angioplasty to obtain good wall apposition as opposed to other studies 10. We have since been using 0.027” catheters (as shown in figure 1B) to deploy the stents in our studies and achieving good self-expansion without the need for angioplasty.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…If the neointimal layer does not cover the bioabsorbable struts evenly, either the stent itself or small segments of PLLA fibers can potentially migrate during fragmentation of polymer in the absorption process, increasing the chance of stroke. The delivery conditions reported in our animal studies resulted in a significant temporary stent diameter reduction of more than four times, yet did not require angioplasty to obtain good wall apposition as opposed to other studies 10. We have since been using 0.027” catheters (as shown in figure 1B) to deploy the stents in our studies and achieving good self-expansion without the need for angioplasty.…”
Section: Discussionmentioning
confidence: 77%
“…In 2019, our group described the first self-expanding bioabsorbable flow-diverting stent for brain aneurysms, which was presented at the 2019 Joint Cerebrovascular Section Meeting 9. More recently, Nishi et al published their pilot data on a biodegradable flow-diverting PLLA stent requiring angioplasty for proper deployment 10…”
Section: Introductionmentioning
confidence: 99%
“…The New Zealand rabbit elastase-induced aneurysm of the RCCA is one of the most common experiment models in testing the safety and efficacy of new endovascular devices in the field of interventional neuroradiology and biomaterial engineering (1)(2)(3)(4)(5)(6). However, the configurations of the aneurysm, especially neck width, still remain randomized and uncontrollable.…”
Section: Discussionmentioning
confidence: 99%
“…The preclinical experiment studies play an important role in helping practitioners and device developers improve techniques and tools for endovascular treatment (EVT) of intracranial aneurysms. Elastase-induced aneurysm of the right common carotid artery (RCCA) in rabbits has been widely used to test the safety and efficacy of new endovascular devices prior to use in humans (1)(2)(3)(4)(5)(6). The previous preclinical studies have indicated that the elastase-induced aneurysm model has similar hemodynamic, morphological, and histologic characteristics to human unruptured aneurysms, and demonstrated similar healing responses and biologic characteristics to treat with coils, stents, and flow diverters as human aneurysms (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…[ 169 ] 2019 X Surgical Rabbits Saccular X X Grüter B.E. [ 170 ] 2019 X Surgical Rats Saccular X Nishi H. [ 171 ] 2019 X Surgical Rabbits Saccular X X Iseki S. [ 172 ] 2019 X Surgical Swines Saccular X King R.M. [ 173 ] 2019 X Surgical Dogs Saccular X X …”
Section: Methodsmentioning
confidence: 99%